Pro-Environmental Behavior: Its Moderating Role on the Relationship Between Environmental Identity and Climate Change Anxiety among Gen Z Filipinos - Reyes, Marc Eric S.; Mapoy, Alvin Joseph D.; Aranzanso, Victoria Ann Louis N.; Avera, Francheska Ysabel A.; Martinez, Beatrice O.; Ramos, Mariah Michaela T.; Cayubit, Ryan Francis O. (Makara Human Behavior Studies in Asia, 2026)
Environmental identity refers to an individual’s understanding of how their environment shapes their identity and relationships. This connection may cause climate change anxiety and motivate pro-environmental behavior. Using an explanatory, cross-sectional design, we examined whether environmental identity (EI) predicts climate change anxiety (CCA) and whether pro-environmental behavior (PEB) moderates their relationship. Seven hundred sixty-one Filipinos aged 18–25 completed the Revised Environmental Identity Scale, Climate Change Anxiety Scale, and Pro-Environmental Behavior Scale. Our findings revealed a significant positive relationship between environmental identity and anxiety about climate change. However, moderation analysis indicated that environmental identity is only associated with climate change anxiety among participants with high pro-environmental behavior. Thus, Gen Z Filipinos who connect more with nature (high EI) experience greater anxiety (high CCA) only for those who actively engage in PEB. This study discusses the practical and theoretical implications of the findings.